SWOT Analysis of the Marketing Mix Strategy of Integrated Heart Services of Pku Muhammadiyah Gamping Hospital in the Era of National Health Insurance - Muhammad Aditya Pratama; Syamsu Hidayat; Rosyidah Rosyidah (Jurnal Indonesia Sosial Teknologi, 2024)
The referral system in the National Health Insurance policy is a challenge for class B hospitals. This research aims to analyze the marketing mix strategy for Cardiac Vascular Center carried out by the PKU Muhammadiyah Gamping hospital in the National Health Insurance era. The research approach used is qualitative with a case study type of research. The subjects of this research are internal hospital informants and were selected based on purposive sampling criteria, namely those related to the marketing strategy of the hospital's superior services. Based on the results of the SWOT analysis, an alternative strategy was obtained, namely a growth oriented strategy. This strategy maximizes the strengths you have to take advantage of existing opportunities or can also be called an SO (strength-opportunity) strategy. The strategies resulting from the SWOT analysis are improving human resources, adding services, developing facilities and infrastructure, increasing promotions, collaborating, improving IT systems, providing HR training and studies, and providing appropriate remuneration. It is hoped that the results of this research can be used as a consideration for strategic decisions for Cardiac Vascular Center at PKU Muhammadiyah Gamping Hospital and for other researchers to make strategic priorities according to hospital needs.